Cutaneous Manifestation of COVID-19: A Short Clinical Case - Ratesh Bassi; Geetika Bassi (International Healthcare Research Journal, 2020)
Much is now known about the respiratory presentation of coronavirus SARS-CoV-2 (COVID-19) but it can also show up with clinical manifestations in other locations, such as on the skin. Herein, we describe a case with cutaneous symptoms that emerged during the recovery phase in a SARS-CoV-2 coronavirus infected patient. It is important for the healthcare professionals as well as the patients to know about such scenarios, so that appropriate action can be readily taken.